PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KELANCARAN PEMBERIAN KREDIT (Studi Kasus Pada PT. Bank Riau Cabang Batam) - Azib Azib; Hizrah Sari Sawitri Sujatmi (Jurnal Manajemen Bisnis Performa, 2007)
Abstract This research has purpose to test how big the affect of goog corporate governance to credit of bank gift on PT. Bank Riau Batam Branch.The method used in this research are descriptive and analytic method, the descriptive method has purpose to make descriptive systematically, actual, and accurate, about facts, characteristics and the relationships between the fenomena which investigated. The data gets by distributing questioners to the labourers of Pt.Bank Riau Batam Branch.The data collected analized by statistic test with used simple regression and person’s correlation (rxy). The propability which used has been 95% (α = 0,05). With partial test has produced that tcount has 10.24 and ttabel 2.03 it’s mean the Ho hypothesis has refuse and the and the hypothesis which the present writer proposed that ha could proved and accepted.Based on the explanation on the top it’s summarized that the good corporate governance prinsipt on PT. Bank Riau Batam Branch has been effective. In this research has the significant relation beetween good corporate governance with the fluent of credits of bank gift. Keyword :Transparancy, indepedency, responsibility, accountability, fairness, trust, time, degree of risk.